Methodology to Evaluate the Residential Electrical Stock Appliances According to Socioeconomic Status - Pérez, Jhon J.; Bernal, EfraÃn; Giraldo, Juan S. (International Journal of Energy Economics and Policy, 2019)
This paper attempts an understanding of the use of stock electrical appliances in the city of Bogot´a D.C. We developed a methodology based on Colombia’s National Quality of Life (NQL) 2016, the methodology uses a questionnaire survey focused on information related to: type of residential building, appliances stock, socioeconomic status and income, among others. The proposed study explains the relationship between appliance stock and socioeconomic status, income, and type of household by using an econometric energy model. The results obtained have a potential application in energy planning strategies and policies, especially for lowest social status. Keywords: Electrical stock appliances, socioeconomic status, econometric energy model. JEL Classifications: C50; D12; Q40 DOI: https://doi.org/10.32479/ijeep.7179